Processo della pelle per la produzione di borse: studio organizzativo, identificazione generale dei pericoli, prevalutazione del rischio per il sovraccarico biomeccanico mediante un nuovo strumento di valutazione di semplice applicazione / Leather bags production: organization study, general identification of hazards, biomechanical overload risk pre-evaluation using an easily applied evaluation tool - Montomoli, L.; Coppola, G.; Sarrini et al., D. (La Medicina del Lavoro, 2011)
«Leather bags production: organization study, general identification of hazards, biomechanical overload risk pre-evaluation using an easily applied evaluation tool». Background: Craft industries are the backbone of the Italian manufacturing system and in this sector the leather trade plays a crucial role. Objective and Methods: The aim of the study was to experiment with a risk pre-mapping data sheet in leather bag manufacture by analyzing the production cycle. Results: The prevalence of biomechanical, organizational and physical factors was demonstrated in tanneries. With regard to chemical agents the lack of any priority of intervention could be due to the lack of information on the chemicals used. In the 2 enterprises that used mechanical processes the results showed different priorities for intervention and a different level of the extent of such intervention. In particular in the first enterprise biomechanical overload was a top priority, while in the second the results were very similar to those of the tannery. The analysis showed in both companies that there was a high prevalence of risk of upper limb biomechanical overload in leather bag manufacture. Chemical risk assessment was not shown as a priority because the list of chemicals used was neither complete nor sufficient. Conclusions: The risk pre-mapping data sheet allowed us to obtain a preliminary overview of all the major existing risks in the leather industry. Therefore the method can prove a useful tool for employers as it permits instant identification of  priorities for intervention for the different risks.